Uji Aktivitas Antioksidan Sediaan Face Mist Ekstrak Daun Pepaya California (Carica papaya L.) dengan Metode DPPH - Jihan Zulfa Nabila; Eny Widhia Agustin (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
Free radicals are a major cause of skin damage that can accelerate premature aging; therefore, the use of antioxidants, particularly from natural sources such as papaya leaves (Carica papaya L.), is essential due to their flavonoid, tannin, and polyphenol content. The application of antioxidants in a face mist formulation is considered practical as it is easy to use and provides a refreshing effect on the skin. This study aimed to evaluate the antioxidant activity of a face mist containing California papaya leaf extract using the DPPH method and to assess its physical characteristics. A quantitative experimental method with a post-test only design was employed using two formulations with different extract concentrations. The results showed that the IC₅₀ values of Formula I and Formula II were 2475.23 ppm and 812.14 ppm, respectively, indicating very weak antioxidant activity, although Formula II exhibited better performance. Physical evaluation revealed that both formulations were organoleptically stable and homogeneous; however, the pH values were below the acceptable skin range and the viscosity of Formula II was relatively high. In conclusion, the formulation demonstrates potential as a natural antioxidant product, but further optimization is required to improve its effectiveness and quality.